Two's a company : An exploration of the ongoing relationship between two people who found and manage businesses together and how that relationship contributes to the survival of their organisation - Jarvis, Penelope (Cranfield University, 1999)
The continuum of desirable leadership skills and attributes ranges from long-term vision to short-term control. It takes a exceptional person to cover such a broad span, yet both leadership and entrepreneurship literature tend to focus on the single leader as superperson' . On the other hand, organisational literature of both growth and survival draws our attention to the potential management crisis occurring when initial entrepreneurial leadership proves inadequate to manage the transition into a more mature organisation thus necessitating either a change of leadership or the demise of the organisation. The need to move between entrepreneurial and conservative management styles which Slevin & Covin (1990) call 'cycling', aptly describes this paradox but their model again concentrates on the individual. Personal observation suggested there were many incidences of a alterative model of successful leadership cycling, namely the founding and leading of a organisation by two people, either affective couples or work associates, thus avoiding the need for changes of leadership as the organisation grows. There has been little empirical research as to whether this is a appropriate model of entrepreneurship/leadership even though this could result in a model of the full leadership continuum. This research attempts to remedy this, focusing on the relationship between joint founder/leaders of organisations, and investigating the effectiveness of this unit of management in relation to the leadership paradox. As statistics indicate that 5 years seems to be the watershed in the survival of new organisations, this study looks at companies founded and managed by two people which have continued and developed beyond that period and seeks to understand what elements in the dyadic relationships may have contributed to the business' continuance. It has as its aim the building of a model of cyclical dyadic leadership which, while set here within the context of business start-up, may well have application within the wider corporate setting. The focus is on the people who choose to work in partnership and their evolving relationship: how and why such a relationship is formed, what were their initial intentions for founding and the effect of that relationship on the organisation. This final thesis is presented as a journey through the process of doing research: it aims to report on and analyse both the findings and elements of the actual research g the way of doing research thus giving insights into both a appropriate way of doing research and also into the chosen subject matter. This stems from a intrinsic belief that research findings and methodology are immediately linked and thus of equal relevance. The research employed a realist ontology and used a grounded theory approach, using a series of longitudinal case studies which employed a variety of methods which were adapted and refined as the themes emerged. The final proposed dyadic leadership model themes can be outlined as follows: Intimacy: The working relationship between the dyad , whether based on marriage, work or friendship, is a intimate relationship and as such introduces emotional elements into the work environment which result in a specic dyadic culture; it is this relationship which is the reason for founding. Commonality: The choice of partner drives the decision to found and it is the commonality of interests, intent and values which is a prerequisite in the choice of partner; commonality drives the later choices of business strategy, and provides the ground rules for the business. 3 Complementarity: Complementarity of skills is a important factor in the decision to found and the early part of the business as it forms the basis for the choice of business activity and the initial allocation of roles; initial allocation of roles is thus based on content skills rather than management skills, and as the business grows, fully complementary roles are needed to sustain the organisation; inappropriate behaviour results from both inappropriate allocation of roles and from problems as the intimate dyadic relationship operates within a work environment; the subsequent development of complementary behaviour and management styles become important for the survival of the organisation. Covergence/Divergence: The initial intentions of the dyad shapes the organisational development by either limiting or facilitating growth; divergence from the original common intent can be disruptive as the organisation develops; divergence can also result in the social context as married couple's relationships become closer both at work and socially while work associates increasingly disassociate work from social activities. Organisational Survival: Dyadic founder/manager relationships result in singular organisations which are strongly influenced by both the emotional and rational elements of the relationship; the dyadic start-up can become a extremely successful organisation when successful cycling of the leadership role takes place between the partners.